(untitled) - Browne, Christopher H. (Hoboken, N.J., 2007)
There are many ways to make money in today's market, but the one strategy that has truly proven itself over the years is value investing. Now, with The Little Book of Value Investing, Christopher Browne shows you how to use this wealth-building strategy to successfully buy bargain stocks around the world.
Keywords: Investment analysis,Stocks,Value investing,Investments,Corporations,Phân tích đầu tư,Cổ phiếu,Vốn đầu tư,Tổng công ty; Valuation,Vốn